Conditional knowledge in stoichiometry’s problem solving - Abdullah Sangguro, Salina (Palarch, 2020)
Conditional knowledge highlights the ways of solving the problem in a real-life setting. Everyday life applies open-ended questions and students need to link conceptual, procedural, and conditional knowledge to solve the problem. Thus, this qualitative research approach assesses the conditional knowledge of stoichiometry’s problem-solving among high school students in Sabah. A total of 172 students from five different schools selected as respondents. The data obtained from one part of an open-ended test named ‘Stoichiometry’s Achievement Level Test’ or UTPSK. There are three categories of implementing conditional knowledge among the students, which are good conditional knowledge, moderate conditional knowledge, and low conditional knowledge. The result shown majority students fall into low implementing of conditional knowledge. Furthermore, students’ alternative framework appeared on each of the questions. It hopes that the findings of this research will provide useful insight into learning for the students and it contributes to the value of conditional knowledge to improve the ability of the students to solve problems in chemistry.